Makna Penuaan Lansia dalam Kearifan Lokal Kampung Naga - Kania Cahyaningtyas; Salma Nur Maulida; Mamat Supriatna; Tri Lestari (CV. ITTC INDONESIA, 2025)
Aging is commonly perceived as a phase of decline characterized by physical deterioration and age-related stigma, which increases psychosocial vulnerability among older adults. This study aimed to explore the meaning of aging among older adults in Kampung Naga by examining the role of local wisdom in shaping physical, psychological, social, and spiritual well-being. A qualitative phenomenological approach was employed. Data were collected through in-depth interviews, participant observation, and documentation involving four participants, including early elderly, late elderly, the oldest-old, and a cultural leader. Data were analyzed using thematic analysis. The findings revealed four interconnected themes: physical–ecological harmony, emotional–spiritual harmony, social–communal harmony, and cultural harmony as the foundation of aging meaning. Older adults in Kampung Naga perceive aging as a natural, dignified, and meaningful life process characterized by acceptance, interconnectedness, and social respect. Cultural values such as hirup sauyunan, silih asih–silih asah–silih asuh, and narima strengthen psychological resilience and sustain social participation. Minimal ageism and strong communal support contribute to a positive aging experience. These findings highlight the significant role of local wisdom in fostering healthy and meaningful aging within Indigenous communities.